Trzy umowy małżeństwa z początków XVI wieku. Przyczynek do świeckiej praktyki zawierania małżeństw w kręgu szlacheckim na przełomie średniowiecza i wczesnych czasów nowożytnych (Tabularium Historiae, 2020)
The article presents the analysis of three selected marital contracts from the early 16th century, concerning marriages between Anna Lisowska and Mikołaj Tomicki (1515), Katarzyna Krotoska and Jan Borek Gostyński (1515), and Barbara Danaborska and Mikołaj Margoński, coming from the Greater Polish middle and higher noble families. It was aimed not only to examine the contents of marital agreements but also the possibilities that sources offer to study them for that period.